Penyusunan Strategi Alternatif Dengan Pendekatan Triple Layer Business Model Canvas di PT Bando Indonesia - Iriando Wijaya; Dikky Indrawan; Rokhani Hasbullah (School of Business, Bogor Agricultural University (SB-IPB), 2023)
PT Bando Indonesia is a manufacturing company that produces power transmission products and experiencing production capacity problems. The aims of this study are (1) to identify and evaluate the influence of the business environment factors and the current business model at PT Bando Indonesia; (2) to examine alternative business strategies applied by PT Bando Indonesia and; (3) to formulate recommendations and managerial implications based on the new business model. The method in this study uses internal analysis (IFE), external analysis (EFE), SWOT, and triple-layer business model canvas (TLBMC). The results show that the company's strengths are consumer segmentation, marketing, and product quality. The company’s weaknesses are procurement of materials, number of employees, and product development facilities don’t exist. The company's opportunities in their business are the growth of green technology, people's lifestyles, and people's awareness of the environment. The study also shows that the company’s threats are inflation, tax, unstable price of materials, and other resources. There are several alternative strategies generated using a SWOT analysis based on the company's internal and external circumstances The alternative strategies formed influence the improvement of the existing business model in several of its constituent factors. The three factors in TLBMC, economic, environmental, and social, received improvements in several of their building blocks to support alternative corporate strategies that have been formed. Keywords: Bando Indonesia, external analysis (EFE), internal analysis (IFE), SWOT, TLBMC